A Comparison between Real and DLA Simulated Liver Lobules using a Population Density Analysis - Wisk, Sara; Rezania, Vahid (MacEwan University Student eJournal, 2016)
A liver lobule is comprised of networks of sinusoids and hepatocytes. Here, a liver lobule was computationally constructed by using diffusion-limited aggregation (DLA) method.  A population density analysis of the sinusoids and hepatocytes was performed and then compared with a real lobule image. The resulting images were compared using a histogram to interpret the ratio of hepatocytes to sinusoids.